2021
DOI: 10.5222/gkdad.2021.05025
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Noninvasive Ventilation, High-Flow Oxygen Therapy and Conventional Oxygen Therapy for Weaning Failure in High-Risk Patients

Abstract: Objective: The most common reason for intensive care unit admission is acute respiratory failure and after extubation mainly three methods are used to bring the PaO2 level to a sufficient level: conventional oxygen therapy (COT), high flow oxygen therapy (HFO), and non-invasive ventilation (NIV). The aim of this study was to determine if NIV or HFO is beneficial in decreasing weaning failure in high-risk patient population (HRP) and compare these noninvasive methods. Methods: This prospective, observational co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Mungan et al conducted a prospective, observational, cohort study to determine the effects of the use of HFNC, conventional oxygen therapy, and non-invasive ventilation (NIV) on weaning failure in high-risk patients and recorded the lowest re-intubation rate along with a reduced ICU stay and hospital stay in the HFNC group. The study also reported that the total mechanical ventilation assistance duration and length of stay in the ICU and hospital differed between groups receiving NIV, HFNC, and conventional oxygen therapy, thus favoring the high-flow oxygen therapy group [21].…”
Section: Discussionmentioning
confidence: 91%
“…Mungan et al conducted a prospective, observational, cohort study to determine the effects of the use of HFNC, conventional oxygen therapy, and non-invasive ventilation (NIV) on weaning failure in high-risk patients and recorded the lowest re-intubation rate along with a reduced ICU stay and hospital stay in the HFNC group. The study also reported that the total mechanical ventilation assistance duration and length of stay in the ICU and hospital differed between groups receiving NIV, HFNC, and conventional oxygen therapy, thus favoring the high-flow oxygen therapy group [21].…”
Section: Discussionmentioning
confidence: 91%